EU security and defence cooperation in times of dissent: analysing PESCO, the European Defence Fund and the European Intervention Initiative (EI2) in the shadow of Brexit. Issue 3 (2nd July 2020) - Sweeney, Simon; Winn, Neil
ABSTRACT: Has the United Kingdom(UK) Brexit referendum been a catalyst for more European Union security cooperation? How significant are post-referendum initiatives in security and defence? What are the implications of Brexit for European Union (EU) and UK security and defence? This article analyses EU post-Brexit strategic choices following the launch of the EU Global Strategy (2016). EU autonomy in security and defence requires close cooperation with third countries, including Norway and post-Brexit UK. It remains to be seen whether the EU and the UK can forge a new bespoke security and defence relationship that delivers mutual benefits through shared strategic ambitions, while also protecting their various interests. We suggest there will be serious collateral damage to UK-EU security and defence cooperation if post-Brexit trade negotiations descend into acrimony and mistrust, especially in the event of "no-deal" once the "transition period" ends. This would undermine European security and the EU's quest for strategic autonomy in world affairs and have serious implications for both UK and EU security. We conclude that the EU needs to work with the UK on a plan to achieve global strategic autonomy, or both risk reduced influence in the wider world in the years ahead.